Pain assessment during physiotherapy and noxious stimuli in patients with disorders of consciousness: A preliminary study - Shen, Jianzhong; Tang, Shanchun; Yan, Bingyang; Xie, Donghua; Fang, Tingting; Chen, Lidan; Li, Guoyun (Frontiers in Integrative Neuroscience, 2022)
Objectives The primary purpose of this study is to determine whether patients with disorders of consciousness (DOC) (unresponsive wakefulness syndrome, UWS; minimally conscious state, MCS) experience pain during physiotherapy and noxious stimuli in a larger patient population. Materials and methods The patients’ level of consciousness was measured with the Coma Recovery Scale-Revised (CRS-R). Additionally, the Nociception Coma Scale-revised (NCS-R) was used to assess their pain response. The NCS-R total scores between UWS and MCS at baseline, physiotherapy and noxious stimulus were compared using the Mann-Whitney U test (Wilcoxon rank-sum test) and the Kruskal-Wallis H test with Bonferroni correction. Results The study enrolled 93 participants. There was a statistically significant difference in NCS-R total scores between the three conditions (H = 215.25, p < 0.001). At baseline, there was no statistically significant difference between MCS and UWS (U = 378, z = –1.35, p = 0.178). While there was a statistically significant difference between MCS and UWS during physiotherapy (U = 1,362, z = –3.06, p < 0.01) and under noxious stimuli (U = 5142.5, z = –11.22, p < 0.001). Conclusion Physiotherapy improved the activity responsiveness of DOC patients, and patients experienced less potential pain. However, some DOC patients, especially MCS patients, perceived pain under the noxious stimuli.